MERANCANG PENDIDIKAN EKONOMI DAN BISNIS ISLAM DI DESA CIARUTEUN ILIR, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Rully Trihantana; Ermi Suryani; Konita Oktaviani Lutfiyah (SAHID DEVELOPMENT JOURNAL, 2023)
Community service in Ciaruteun Ilir Village is designing an Islamic economics and business lesson with the following learning designs: providing socialization, learning together about Islamic economics and business, because Islamic economics is basically an economy that makes the human soul a strong, creative and creative soul. also innovative so that the economy in this area becomes more advanced and develops so that the residents in Ciaruteun village are not only spinach and kale farmers who usually enter their goods into markets in Bogor. The place for community service this time is located in the Ciaruteun Ilir area, Cibungbulang district, Bogor district, West Java. So that the result of a prospective design for the future is to make a group of processing practices from spinach and vegetables to become other items that are useful and in demand by many people.